Umbilical Cord Blood-Derived Stem Cells Improve Heat Tolerance and Hypothalamic Damage in Heat Stressed Mice. (7th April 2014) - Tseng, Ling-Shu; Chen, Sheng-Hsien; Lin, Mao-Tsun; Lin, Ying-Chu
Abstract : Heatstroke is characterized by excessive hyperthermia associated with systemic inflammatory responses, which leads to multiple organ failure, in which brain disorders predominate. This definition can be almost fulfilled by a mouse model of heatstroke used in the present study. Unanesthetized mice were exposed to whole body heating (41.2°C for 1 hour) and then returned to room temperature (26°C) for recovery. Immediately after termination of whole body heating, heated mice displayed excessive hyperthermia (body core temperature ~42.5°C). Four hours after termination of heat stress, heated mice displayed (i) systemic inflammation; (ii) ischemic, hypoxic, and oxidative damage to the hypothalamus; (iii) hypothalamo-pituitary-adrenocortical axis impairment (reflected by plasma levels of both adrenocorticotrophic-hormone and corticosterone); (iv) decreased fractional survival; and (v) thermoregulatory deficits (e.g., they became hypothermia when they were exposed to room temperature). These heatstroke reactions can be significantly attenuated by human umbilical cord blood-derived CD34 + cells therapy. Our data suggest that human umbilical cord blood-derived stem cells therapy may improve outcomes of heatstroke in mice by reducing systemic inflammation as well as hypothalamo-pituitary-adrenocortical axis impairment.